Frontiers in Operations: Last-Mile Delivery in Healthcare: Drone Delivery for Blood Products in Rwanda - Jeon, H. Harriet; Lucarelli, Claudio; Mazarati, Jean Baptiste; Ngabo, Donatien; Song, Hummy (Manufacturing and Service Operations Management, 2026)
Problem definition: Last-mile delivery is one of the most challenging and costly facets of the supply chain. Using data from Rwandan public hospitals that transfuse blood, we examine whether and the extent to which the adoption of a technological innovation—delivery drones—for the last-mile delivery of blood products impacts the way hospitals manage the inventory of these products and the downstream health outcomes for patients. Methodology/results: To estimate causal effects, we exploit the staggered rollout of the drone delivery system and use a generalized difference-in-differences approach. We find that all hospitals, regardless of their distance to the drone port, substantially decrease their on-hand inventory of red blood cells, most notably for the most flexible product (i.e., type O blood). Hospitals also meaningfully reduce their wastage of red blood cells, especially for “in-between” products that are neither the most flexible nor the least flexible (i.e., type B blood). With respect to patient health outcomes, we document large reductions in in-hospital mortality for two health conditions where timely access to blood is a critical input for treatment: postpartum hemorrhage and trauma. Interestingly, this change is concentrated among hospitals closer to the drone port, and these are the same set of hospitals that increase the transfusion of blood products. This increase is especially pronounced among blood products that cannot be held in stock at the hospital, including platelets and fresh frozen plasma. Managerial implications: Our results highlight key considerations for decision makers allocating scarce resources to improve hospital operations and health outcomes. Given that health improvements are not realized by all hospitals, operational decisions—such as the number and location of drone ports—should ensure clinically meaningful delivery windows for time-sensitive medical care. History: This paper has been accepted in the Manufacturing & Service Operations Management Frontiers in Operations Initiative. Funding: This work was supported by the Wharton Dean’s Research Fund, Wharton Global Initiatives Research Program, Claude Marion Endowed Faculty Scholar Award, Mack Institute Research Fellowship, and Fishman-Davidson Center for Service and Operations Management. Supplemental Material: The online appendix is available at https://doi.org/10.1287/msom.2025.0055 .